1997
DOI: 10.1111/1468-005x.00020
|View full text |Cite
|
Sign up to set email alerts
|

E‐mail, Power and the Constitution of Organisational Reality

Abstract: To many observers, the introduction of electronic mail into a business organisation is an undramatic affair which is likely to have little impact beyond that on intra‐organisational communication. Using insights from actor‐network theory, this article demonstrates the more insidious and far‐reaching impact of electronic mail on organisational power relations, knowledge and employee behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 1 publication
2
22
0
1
Order By: Relevance
“…Ciborra and Hanseth (1998) invoked Heidegger alongside actor-network theory in their work on information infrastructures. Knights et al (1997) drew on Foucault in their study of computer networks in the nancial services industry, as did Brigham and Corbett (1997) in their discussion of how electronic mail is implicated in organizational power relations and control at a distance. Even Latour (1996) seemed to hint that something else needs to be added to the network when asked to provide policy or pass judgement.…”
Section: Ontological Considerationsmentioning
confidence: 99%
“…Ciborra and Hanseth (1998) invoked Heidegger alongside actor-network theory in their work on information infrastructures. Knights et al (1997) drew on Foucault in their study of computer networks in the nancial services industry, as did Brigham and Corbett (1997) in their discussion of how electronic mail is implicated in organizational power relations and control at a distance. Even Latour (1996) seemed to hint that something else needs to be added to the network when asked to provide policy or pass judgement.…”
Section: Ontological Considerationsmentioning
confidence: 99%
“…Our study of the VMDS has demonstrated how people, organisation and technology shape each other and hold each other in place: the VMDS illustrates how brigade actors are concerned with framing understanding of reality and imposing these understandings on each other. The VMDS is not simply a medium for access to information 'anywhere and anytime' but is implicated in the constitution of reality and identities -IT does have power, most importantly the power to transform what counts as important (see also Brigham and Corbett, 1997). From this we suggested that the VMDS enframes information and communication by defining it as technological and as such improvisation itself is set within a calculative and instrumental form of thought.…”
Section: Improvisation and Bricolage: Spatial And Temporal (Dis)connementioning
confidence: 98%
“…According to ANT, the social nature is made of human and non-human actors (Akrich & Latour 1992;Brigham & Corbett, 1997), with both having the capacity to act upon or alter the other (Law, 1984) and each other's courses of action (Durepos & Mills, 2012). Within a MOOC perspective, ANT provides and understanding on how the social and technological dimensions are embedded in each other (Deimann, 2014).…”
Section: Actor Network Theory (Ant)mentioning
confidence: 99%